Considerations about foxing stains in three paper collections ranging from the 16th to the 20th century - Figueira, Francisca (2020)
Three surveys on the occurrence of foxing stains were carried out on papers dating from 1560 to 1975 in three Portuguese collections. Foxed papers were found to be more intensely and intrusively stained in certain time periods of each collection. Based on historical data and the professional paper conservation expertise, the authors linked the increased occurrence of foxing stains in certain time periods to the new papermaking processes and materials, which began to be introduced in the late 18th century, and in particular to a synergistic effect between three factors: the use of deficient gelatine sizing which began to present a poorer quality and homogeneity, the presence of iron-containing impurities throughout the paper leaf and a distinct absorbency of moisture. Observing batches of morphologically similar papers by using photographic imaging with different types of light sources and incidences, the authors verified that similar papers present similar foxing stains.   Received: 2019-7-20 Revised: 2019-11-19 Accepted: 2019-11-27 Online: 2020-5-4 Publication: 2020-11-27